Hydrogen sulfide protects colon cancer cells from chemopreventative agent β-phenylethyl isothiocyanate induced apoptosis - Rose, Peter (World J Gastroenterol, 2005)
AIM: Hydrogen sulfide (H(2)S) is a prominent gaseous constituent of the gastrointestinal (GI) tract with known cytotoxic properties. Endogenous concentrations of H(2)S are reported to range between 0.2-3.4 mmol/L in the GI tract of mice and humans. Considering such high levels we speculate that, at non-toxic concentrations, H(2)S may interact with chemical agents and alter the response of colonic epithelium cells to such compounds. The GI tract is a major site for the absorption of phytochemical constituents such as isothiocyanates, flavonoids, and carotenoids, with each group having a role in the prevention of human diseases such as colon cancer. The chemopreventative properties of the phytochemical agent β-phenyethyl isothiocyanate (PEITC) are well recognized. However, little is currently known about the physiological or biochemical factors present in the GI tract that may influence the biological properties of ITCs. The current study was undertaken to determine the effects of H(2)S on PEITC mediated apoptosis in colon cancer cells. METHODS: Induction of apoptosis by PEITC in human colon cancer HCT116 cells was assessed using classic apoptotic markers namely SubG1 population analysis, caspase-3 like activity and nuclear fragmentation and condensation coupled with the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrasodium bromide] viability assay and LDH leakage. RESULTS: PEITC significantly induced apoptosis in HCT116 cells as assessed by SubG1 population formation, nuclear condensation, LDH leakage and caspase-3 activity after 24 h, these data being significant from control groups (P < 0.01). In contrast, co-treatment of cells with physiological concentrations of H(2)S (0.1-1 mmol/L) prevented PEITC mediated apoptosis as assessed using the parameters described. CONCLUSION: PEITC effectively induced cell death in the human adenocarcinoma cell line HCT116 in vitro through classic apoptotic mechanisms. However, in the presence of H(2)S, apoptosis was abolished. These data suggest that H(2)S may play a significant role in the response of colonic epithelial cells to beneficial as well as toxic agents present within the GI tract.